Students’ Need Analysis on Critical Reading Learning Material at English Department of Universitas Negeri Padang - Cinto Dwi Asyura; Fitrawati Fitrawati (Universitas Negeri Padang, 2021)
To achieve the objective of learning especially in critical reading course, it is important to provide a good teaching material. One of the important things to do before developing the materials is analyzing the needs of the students. This study aims to analyze studens’ needs on critical reading learning material at English department of UNP. This research was a descriptive study using a quantitative approach with the data collection technique using the combination of closed-ended and open-ended questionnaire. The respondents in this study were 80 students from 2018 at English Department of Universitas Negeri Padang who had taken critical reading course. They were given 25 closed-ended questions and three open-ended questions. The results showed that in the aspect The Important of Topic Variation was categorized as “very important” (82%), The Importance of Tasks in Critical Reading was categorized as “important” (81%), Topic for Critical was categorized as “important”. There were 96.25% students expected to have the improvement in the term of topics in Critical Reading Materials. There were 80% students wanted the improvement in the aspect of tasks. Then, 50% of 80 students wanted the improvement in term of skills.